ChemInform Abstract: Manganese‐Mediated Alkene Chloro‐phosphinoylation. Issue 40 (October 2015) - Richard, Vincent; Fisher, Henry C.; Montchamp, Jean‐Luc
Abstract The bisfunctionalization of alkenes with phosphorous and chlorine to afford β‐chloro‐phosphinoyl compounds is described.